Characteristics of skin aging at the Dermatology and Venereology Outpatient Unit at Prof. dr. I Goesti Ngoerah Gde Ngoerah General Hospital, Denpasar from January to December 2019 - Tiara Evangelista; Ni Made Dwi Puspawati; Luh Made Mas Rusyati; I Gusti Ayu Agung Praharsini (Explorer Front, 2023)
Background: Skin aging is a complex biological process influenced by intrinsic and extrinsic factors. In addition, national data regarding skin aging is still scant. This research was carried out to learn the characteristics of skin aging at the Dermatology and Venereology outpatient unit of Prof. Dr. I G. N. G. Ngoerah General Hospital, Denpasar, in January-December 2019. Methods: This research is a quantitative descriptive study with a cross-sectional design. Sampling was carried out by total sampling with research subjects consisting of skin-aging patients at the Dermatology and Venereology Outpatient Unit of Prof. dr. I G. N. G. Ngoerah General Hospital in January-December 2019. The data collected consists of age, gender, smoking history, alcohol consumption history, body mass index, usage of sunscreen, duration of sun exposure, and Glogau scale classification. Descriptive analysis was carried out using SPSS ver. 23. Results: Twenty cases of skin aging were included. Most cases of skin aging were in the age group of 36-45 years old, all of whom were female, all of whom had no history of smoking, all of whom had no history of alcohol consumption, most body mass index classification was overweight, most do not use sunscreen, the duration of the sun exposure is mostly 30 minutes-6 hours, and the highest classification of the Glogau scale is group III. Conclusion: In this study, body mass index, usage of sunscreen, and duration of sun exposure are the main factors affecting skin aging.